GOVERNING FINANCIAL DATA IN THE SAP S/4HANA ENVIRONMENT: SECURITY, COMPLIANCE, AND SCALABILITY CONSIDERATIONS - Anandakumar Sundaramoorthy (INTERNATIONAL JOURNAL OF COMPUTER ENGINEERING AND TECHNOLOGY, 2025)
Migration from the existing SAP FI to SAP S/4HANA proves to be a governance, security, and scalability challenge coupled with the ability to have real time analytics on the financial data. In this study, best practices are discussed in governing financial information within SAP S/4HANA by case study, specifically regulated industries. The findings suggest that there is a critical need for solving that problem by using integrated approaches that constrain IT governance, GDPR and SOX type of compliance standards, and scalable architectures to allow for sustainable, secure digital finance transformation.